Educação cooperativista e sua importância na manutenção do cooperado: o caso da Cooperativa Agroindustrial C. Vale - Staback, Daiane Franciele (2020)
Because cooperativism is one of the organizational models that promotes economic and social development, studies of solutions that lead to increased performance and reduced problems are increasingly important. Cooperatives are not only looking for improvements in management and their finances, but, mainly in the planning of cooperative education programs that aim at the participation and permanence of their members, as well as the search for new members. Thus, the purpose of this research was to analyze the relationship between cooperative education and the participation and permanence of members of the Cooperativa Agroindustrial C.Vale, headquartered in the city of Palotina Paraná, in selected cities in the micro region of Toledo Paraná. The methodology used was the case study through an exploratory study in five cities in the micro region of Toledo Paraná that owns units of C. Vale. Through the application of questionnaires it was possible to identify that the members know and participate in part of the cooperative education programs organized by C.Vale. Specifically in this research it was possible to verify that cooperative education is recognized as an important way of preserving cooperative doctrine.